Functional Characterization of the Mannitol Promoter of Pseudomonas fluorescens DSM 50106 and Its Application for a Mannitol-Inducible Expression System for Pseudomonas putida KT2440 - Hoffmann, Jana; Altenbuchner, Josef (PloS one, 2015)
A new pBBR1MCS-2-derived vector containing the Pseudomonas fluorescens DSM10506 mannitol promoter PmtlE and mtlR encoding its AraC/XylS type transcriptional activator was constructed and optimized for low basal expression. Mannitol, arabitol, and glucitol-inducible gene expression was demonstrated with Pseudomonas putida and eGFP as reporter gene. The new vector was applied for functional characterization of PmtlE. Identification of the DNA binding site of MtlR was achieved by in vivo eGFP measurement with PmtlE wild type and mutants thereof. Moreover, purified MtlR was applied for detailed in vitro investigations using electrophoretic mobility shift assays and DNaseI footprinting experiments. The obtained data suggest that MtlR binds to PmtlE as a dimer. The proposed DNA binding site of MtlR is AGTGC-N5-AGTAT-N7-AGTGC-N5-AGGAT. The transcription activation mechanism includes two binding sites with different binding affinities, a strong upstream binding site and a weaker downstream binding site. The presence of the weak downstream binding site was shown to be necessary to sustain mannitol-inducibility of PmtlE. Two possible functions of mannitol are discussed; the effector might stabilize binding of the second monomer to the downstream half site or promote transcription activation by inducing a conformational change of the regulator that influences the contact to the RNA polymerase.